The Relationship Between Inauthentic Self-Presentation and Identity Confusion on Second Instagram Accounts Among Early Adulthood in Bekasi City - Rahayu citra; Arfian Arfian; Rijal Abdillah (Journal of Health and Multidisciplinary Health Studies, 2026)
The use of second Instagram accounts among emerging adults provides a space to express identities that differ from those presented on their main accounts. However, this practice may also increase inauthentic self-presentation, which is associated with identity confusion. This study aimed to examine the relationship between inauthentic self-presentation and identity confusion among second Instagram account users in Bekasi City. Data were collected using the Presentation of Online Self Scale (POSS) and the Dimensions of Identity Development Scale (DIDS). The findings revealed a positive and significant relationship between inauthentic self-presentation and identity confusion. Individuals who showed a greater tendency to present themselves inauthentically on their second Instagram accounts also experienced higher levels of identity confusion. Nevertheless, the contribution of inauthentic self-presentation to identity confusion was relatively small, indicating that other factors also influence identity development during emerging adulthood. These findings contribute to the fields of developmental psychology and digital media psychology by providing a better understanding of identity dynamics among social media users.